The Effect of Different Opioids on Acid-Base Balance and Blood Gas Analysis in Hospitalized Dogs - Quintavalla, Fausto; Spindler, Kevin Pascal; Aldigeri, Raffaella; Fidanzio, Francesca (Frontiers in Veterinary Science, 2022)
Pain management is central to veterinary practice, contributing to successful case outcomes and enhancement of the veterinarian-client-patient relationship. Analgesic drugs represent one of the pillars of the multimodal approach to acute and chronic pain management. In dogs the most used opioids are methadone, buprenorphine and tramadol. Several episodes of hypoglycemia in people treated with tramadol and methadone have recently been described. The aim of this work is to evaluate the changes in the glycemic and acid-base balance induced by tramadol, methadone and buprenorphine in hospitalized dogs. A retrospective review of the medical records of dogs hospitalized for both medical and surgical reasons was performed. During 2018-2020, a total of 876 canine patients were treated with opioids, including 228 with tramadol, 273 with methadone and 375 with buprenorphine. Of all these dogs, only a small percentage met the inclusion criteria presented in the initial design. All the hospitalized animals were monitored daily through clinical examination and blood sampling. Blood samples were obtained before opioid administration (T0), and 24 hours (T1) and 48 hours (T2) after opioid administration. The following parameters were evaluated: blood gas value (pH, pCO2), acid-base state (cHCO3), oxymetric values (ctHb, haematocrit), electrolyte values (K+, Na+, iCa, Cl-) and metabolic values (glucose, lactate, anion GAP K+c). The glycemic value in enrolled dogs showed a decrease over time, regardless of the type of opioid used, but remained within the physiological range. The highest average glycemic drop was recorded for methadone, between T0 and T1, followed by tramadol between T1 and T2, while buprenorphine recorded the highest overall glycemic drop between T0-T2 when compared to the other two opioids. Female dogs showed the greatest drop in glycemic value. Lactate concentration always presented values beyond the physiological range at an early stage, which then normalized quickly. Measurement of electrolyte concentrations showed a consistent increase in the values of iCa, Na and Cl. In hospitalized dogs treated with opioids monitoring of gas analytic parameters is important and more attention should be paid to patients hospitalized with certain metabolic and endocrine diseases.